Technology enablers to increase students’ intention to use E-learning system - Osman B Ghazali, Norah Zafer Alduhaim, Azizah Bt Haji Ahmed (Journal of Computing Technologies and Creative Content, 2019)
this study investigated the tangible enablers to motivate students to use e-learning system. There is a lack of knowledge regarding the tangible enablers that are not subjective. This study investigated this with sample of Saudi students, particularly, from Riyadh. This study found out there are four main enablers: self-efficacy, infrastructure, e-sources, and university support that influence considerably student’s intention to use e-learning system in their university.